Teori Kepribadian Jung Dalam Perkembangan Kepribadian Berdasarkan Perspektif Multibudaya - Saraswati, Aulia Rizkika; Ramadhan, Rita Munifah; Rahman, Muhammad Rizal Aulia; Bakhrudin All Habsy (Sociocouns: Journal of Islamic Guidance and Counseling, 2024)
Carl Jung's theory of personality is the existence of a totality of personality called the psyche, which consists of a number of different but interconnected systems that greatly determine a variety of human behavior, thoughts, feelings and activities. This theory contains the unconscious, conscious and archetypes which are very useful for counseling techniques about behavior determined by cultural, biological or instinctive motivations. This research aims to understand the theory of personality in development expressed by Carl Jung and can help explain psychoanalytic counseling from a multicultural perspective. The method used is a qualitative method with a literature study accompanied by provision of journal sources made no more than the last 10 years. The final result of this research is to discuss theories and types of development according to Carl Jung, the structure of personality development, and Jung’s personality theory from a multicultural perspective.